Branching pattern effect and co-assembly with lipids of amphiphilic Janus dendrimersomes - Yang, Yan-Ling; Sheng, Yu-Jane; Tsao, Heng-Kwong (Physical chemistry chemical physics : PCCP, 2018)
The influence of the branching patterns on the membrane properties of Janus dendrimers in water has been investigated by dissipative particle dynamics simulations. The hydrophobic fluorinated dendron (R F ) contains three types of branching patterns, including 3,4-, 3,5-, and 3,4,5-R F . Consistent with experimental results, the hydrophobic layer thickness ( H B ) follows the order: 3,5-R F < 3,4-R F < 3,4,5-R F , which can be explained by the extent of interdigitation (Δ h ): 3,5-R F > 3,4-R F > 3,4,5-R F . Moreover, the 3,4,5-R F membrane shows the highest stretching modulus ( K A ) and the lowest lateral diffusivity ( D ). The 3,5-R F membrane is similar to the 3,4-R F membrane but exhibits a higher K A and smaller D . For the nano-sized dendrimersome, its bilayer thickness is less than that of the planar membrane due to its larger extent of interdigitation. The co-assembly of dendrimersomes with lipids has been studied as well. The thickness and the extent of interdigitation of the lipid-rich domain for the hybrid membrane are significantly affected by the lipid concentration ( l ) and the branching patterns. As l increases, the thickness of the lipid-rich domain grows corresponding to the decrease of interdigitation of the lipid-rich domain. The influence of the branching patterns on the membrane properties of Janus dendrimers in water has been investigated by dissipative particle dynamics simulations.